Reactions to online learning from novice students in two distinct programs. - Dixon, Kathryn; Pelliccione, L. (2004)
Developments in information and communication technologies (ICT) have been rapid in recent years and have promised improved education and training to an increasingly diverse cohort of students. While it is increasingly important for universities to implement a growing array of online courses in order to remain economically competitive, questions remain regarding pedagogical issues, economic costs, philosophical issues, policy issues and personal issues such as student preference for online versus face to face delivery. This paper reports on an investigation which aimed to provide a greater understanding of online learning through the eyes of higher education students in two very distinct courses (undergraduate and postgraduate). An instrument was designed to gather data on the students' prior experience and perceptions of online learning environments. The findings revealed that students are entering the University as technically competent and confident people who expect to utilise technology in their learning environment. Students in both groups indicated that the most important feature of the opportunity to work online was the flexibility this approach allowed in terms of being able to study in their own time and in other environments such as home. They also identified that this mode of delivery enabled them to enhance their learning.